Fourth Five-Year Plan Madras State Programme for 1967-68 - Planning Commission (Planning Commission, 1967)
This volume aims at presenting the tentative Fourth Plan Provision (1966-67 to 1971-72), the anticipated Plan expenditure for 1966-67 and the Plan that emerges out of the Budget Estimates (Revised) for 1967-68 as now presented. 2. The expenditure included in the Plan is only such expenditure as is needed for developmental activity over the level attained at the commencement of the Plan period. The expenditure on maintaining the levels of services started in the First, Second and Third Plans is treated as Committed expenditure and shown as non-Plan expenditure. Thus the outlay included in the Fourth Plan is over and above such committed expenditure.
Finance Department Government of Madras
Finance Department Government of Madras